Monitoring 30° Head Elevation to Enhance Cerebral Perfusion in Traumatic Brain Injury Patients - Syaharuddin; Fardi; Tri Damayanti (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Introduction: Traumatic Brain Injury (TBI) is one of the critical conditions that requires quick and appropriate treatment to prevent further damage to brain tissue. One non-invasive approach that can be applied is a head elevation of 30°, which is believed to increase cerebral tissue perfusion and reduce intracranial pressure. This study aims to evaluate the effectiveness of monitoring and the application of 30° head elevation in improving cerebral perfusion in patients with captive trauma. Research Methodology: This study uses an observational design with a pre-post test approach. The study subjects were patients with capitis trauma who performed a 30° head elevation action. Parameters observed before and after the intervention included the Glasgow Coma Scale (GCS), blood pressure, body temperature, pulse, pain, frequency of vomiting, nausea intensity, and dizziness level. Result: After applying a head elevation of 30°, the patient's GCS remained stable at a value of 15 (Coma Scale). Body temperature decreased from 38.6°C to 36.8°C, and pulse rate from 118x/min to 80x/min. The pain scale decreased from 8 to 3, vomiting from 5x/day to 1x/day, nausea from a score of 5 to 1, and dizziness from a score of 4 to 1. Blood pressure did not change significantly (140/90 mmHg). Conclusion: The application and monitoring of 30° head elevation are effective in increasing the perfusion of cerebral tissue and lowering clinical symptoms related to capitis trauma. This intervention can be used as the first step in the nursing management of TBI patients